Creation of accurate 3D models of harbor porpoises (Phocoena phocoena) using 3D photogrammetry. Issue 2 (11th November 2020) - Irschick, Duncan J.; Martin, Johnson; Siebert, Ursula; Kristensen, Jakob H.; Madsen, Peter T; Christiansen, Fredrik
Abstract: Creating accurate 3D models of marine mammals is valuable for assessment of body condition, computational fluids dynamics models of locomotion, and for education. However, the methods for creating 3D models are not well‐developed. We used photography and video to create 3D photogrammetry models of harbor porpoises ( Phocoena phocoena). We accessed one live adult female (155.5 cm total length), and two dead animals, one juvenile (110 cm total length) and one calf (88 cm total length). We accessed the two dead individuals through a stranding network in Germany, and the live individual through the Fjord and Baelt research center in Denmark. For all porpoises, we used still photographs from hand‐held cameras, drone video, and synchronized GoPro videos to create 3D photogrammetric models. We used Blender software, and other 3D reconstruction software, to recreate the 3D body meshes, and confirmed the accuracy of each of the 3D body meshes by comparing digital measures on the 3D models to original measures taken on the specimens. We also provide a colored, animated version of the live harbor porpoise for educational purposes. These open‐access 3D models can be used to develop methods to study body morphometrics and condition, and to study bioenergetics and locomotion costs.